SJENA MOJE MAME: NARATIVI O DEMENCIJI - Zlomislić, Jadranka (Anafora, 2024)
The choice of the topic for this paper is personal. I started writing the paper as a caregiver to a mother with dementia. In an effort to maintain communication with my mother, I researched medical literature for advice. But I also researched narratives about similar experiences of others to help me understand the disease and how best to be a caregiver. My research evolved into a project to raise awareness about the importance of telling the stories of both patients and caregivers. Two books of caregivers’ personal narratives about dementia provided models for how a caring storyteller can understand the disease and adapt to life with dementia. The narratives in Alzheimer: Twelve Anecdotes and Alzheimer’s in my Home: True Family Stories model how a caring storyteller – instead of a sick “wounded storyteller” (Frank)  can, by transferring one’s own experience in a coherent narrative, confirm the moral and intellectual integrity of the sick person threatened by the loss of communication skills. Unfortunately, the paper was interrupted by the death of my mother. I continued to write during the grieving process, trying to compile in this paper my own knowledge and experiences about dementia, to present ways in which I sought to (bibliotherapy, institutional, narrative) maintain the communication bond with my mother. From an analytical point of view, I continued to write to promote stories about dementia as what has been termed as “narrative of experience” (Labov) of patients and caregivers. To the stories of others, I added my own story of a sick mother, which confirmed that narrative reconstruction can be an effective method for overcoming the feeling of helplessness of caregivers in the face of what Frank calls the “chaos narratives” of the ill. Caregivers’ stories about dementia diseases help to build the collective voice of patients and thus remove the stigma that accompanies them in society. They can be useful for doctors as “formal caregivers” and family members as “informal caregivers” who try to maintain communication with their loved ones. They can also serve as a paradigm for cultural anthropological, literary, folkloristic, and related research that deals with illness narratives. I wrote this paper with the hope that it can help caregivers in similar situations, and the very act of writing was – after the death of my mother  a self-therapeutic method of dealing with the loss of a loved one.